2020
DOI: 10.3390/nu13010096
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutritional Factors and Intestinal Microbiota in Rheumatoid Arthritis Development

Abstract: Evidence about the role of nutritional factors and microbiota in autoimmune diseases, and in rheumatoid arthritis (RA) in particular, has grown in recent years, however many controversies remain. The aim of this review is to summarize the role of nutrition and of the intestinal microbiota in the development of RA. We will focus on selected dietary patterns, individual foods and beverages that have been most consistently associated with RA or with the occurrence of systemic autoimmunity associated with RA. We w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 146 publications
(200 reference statements)
0
18
0
Order By: Relevance
“…Several studies have recently suggested that the use of omega-3 and moderate alcohol consumption may have a protective effect on RA development, particularly among smokers or individuals at high risk, as discussed by Alpízar-Rodríguez D et al in the present Issue [4].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Several studies have recently suggested that the use of omega-3 and moderate alcohol consumption may have a protective effect on RA development, particularly among smokers or individuals at high risk, as discussed by Alpízar-Rodríguez D et al in the present Issue [4].…”
mentioning
confidence: 77%
“…The modification of microbiota using dietary interventions and focusing on the improvement of the intestinal barrier function may become an important component for "preventive" nutritional strategies. Therefore, as a matter of fact, it seems possible that high salt consumption or sugar sweetened soda, for example, may have a negative effect on gut microbiota, increasing the presence of Prevotella copri strains with higher Branced Chain Amino Acids (BCAA) and Lactobacillus depletion resulting on higher intestinal inflammation [4]. Conversely, omega-3, the Mediterranean diet, probiotics and fiber-rich diets exert positive effects on gut microbiota, favoring Prevotella Copri strains with higher potential for carbohydrate degradation and increased short-chain fatty acids (SCFA) synthesis, leading to less intestinal inflammation in RA patients [4].…”
mentioning
confidence: 99%
“…Microbiome as a Potential Therapeutic Target for RA Different dietary patterns could influence the composition and function of the gut microbiome [155]. In a nested case-control study, the individuals at risk of RA had lower concentrations of omega-3 fatty acids in red blood cell membranes, which indicated a potential beneficial effect of omega-3 fatty acids on RA-related autoimmunity [156].…”
Section: Dietary Modification and Gutmentioning
confidence: 99%
“…Potent effects of alcohol on autoimmunity have also been observed in other diseases such as systemic lupus erythematosus (SLE), autoimmune diabetes, Graves' hyperthyroidism, and autoimmune hypothyroidism [30][31][32][33][34]. Of note, nutrition in general has been shown to have strong effects on autoimmunity; in a study of alcohol-use and SLE, there was a significant correlation of wine but not beer consumption as a protective factor [31,35]. A recent review of the possible links between different beverages and RA discussed one of the compounds found in wine, resveratrol, inhibiting downstream mechanisms of TNF receptor [36].…”
Section: Introductionmentioning
confidence: 99%